Design of an Improved Differentially Fed Antenna Array for RF Energy Harvesting - Kumar D.; Chaudhary K. (My University, 2025)
This work presents an enhanced rectenna with differentially fed antenna array for RF energy harvesting. First, a linear antenna array is designed considering its side lobes less than −20 dB. Two antenna array, one with a single feed and other with differential feed, is designed to operate at 5.8 GHz. The measured peak gain of single fed and differentially fed is 13.38 and 14.29 dBi, respectively, at 5.8 GHz. The two antenna array, one with a single feed and other with differential feed, is tested for RF energy harvesting. It is observed that the differentially fed rectenna has higher output DC power than the single fed rectenna. The differentially fed rectenna has higher efficiency as compared with single fed rectenna for the power density variation from 5 to 238 µW/cm2, it has maximum efficiency (RF-DC) of 82.4% at 232 µW/cm2. © 2020, © 2020 IETE.